If p = (2-√5)/(2+√5) and q = (2+√5)/(2-√5):

If p = (2-√5)/(2+√5) and q = (2+√5)/(2-√5), find the values of

(i) p + q
(ii) p – q
(iii) p2 + q2
(iv) p2 – q2

Solution:

Given:
p = (2-√5)/(2+√5) and q = (2+√5)/(2-√5)
(i) p + q
[(2-√5)/(2+√5)] + [(2+√5)/(2-√5)]
So by rationalizing the denominator, we get
= [(2 – √5)2 + (2 + √5)2] / [22 – (√5)2]
= [4 + 5 – 4√5 + 4 + 5 + 4√5] / [4 – 5]
= [18]/-1
= -18
(ii) p – q
[(2-√5)/(2+√5)] – [(2+√5)/(2-√5)]
So by rationalizing the denominator, we get
= [(2 – √5)2 – (2 + √5)2] / [22 – (√5)2]
= [4 + 5 – 4√5 – (4 + 5 + 4√5)] / [4 – 5]
= [9 – 4√5 – 9 – 4√5] / -1
= [-8√5]/-1
= 8√5
(iii) p2 + q2
We know that (p + q)2 = p2 + q2 + 2pq
So,
p2 + q2 = (p + q)2 – 2pq
pq = [(2-√5)/(2+√5)] × [(2+√5)/(2-√5)]
= 1
p + q = -18
so,
p2 + q2 = (p + q)2 – 2pq
= (-18)2 – 2(1)
= 324 – 2
= 322
(iv) p2 – q2
We know that, p2 – q2 = (p + q) (p – q)
So, by substituting the values
p2 – q2 = (p + q) (p – q)
= (-18) (8√5)
= -144√5

More Solution:

Leave a Comment